PERANAN BEA DAN CUKAI DALAM MENANGGULANGI PEREDARAN BARANG ELEKTRONIK ILEGAL BERDASARKAN UNDANG –UNDANG NOMOR 17 TAHUN 2006 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 10 TAHUN 1995 TENTANG KEPABEANAN DI PEKANBARU - Yudha Kurniawan; Erdianto '; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Community needs at this time always menigkat, one of the needs of electronic goods. The high level of demand for electronic goods has a negative impact, such as the criminal smuggling of illegal imported electronic goods. The criminal act of smuggling of imported electronic goods often occurs in the ports of rats that always escape from the supervision of Customs and Excise. Therefore, it is necessary to have an ideal role of Customs and Excise in handling criminal acts of smuggling of illegally imported electronic goods. The purpose of this thesis is to know the role of Customs and Excise in handling the criminal acts of smuggling of illegal imported electronic goods and to know what barriers experienced by Customs and Excise in handling criminal acts smuggling of illegal imported electronic goods in Pekanbaru City. This type of research can be classified in the type of sociological juridical research, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted in jurisdiction of Pekanbaru city, whereas population and sample are all parties related to the problem studied in this research, data source used, primary data, secondary data, and tertiary data, data collecting technique in this research with interview And literature review. From the results of the research that the authors do can be concluded, First the role of Customs and Excise in handling criminal smuggling cases of illegal imported electronic goods is to take measures such as termination, inspection, prevention, and sealing and take the necessary action in the form of not serving the subscriber or the sign of repayment Other excise duties. The two obstacles of Customs and Excise in handling criminal cases of smuggling of illegal imported electronic goods are the area that is unreachable by the officers, the number of popping port of rat, the lack of public awareness about the importance of excise tax, the condition of domestic industry that has not been able to compete with foreign and less The ability of officers to master foreign languages, and less number of guard officers Keywords: Role-Crime-Smuggling-Electronic Merchandise Import